miR‐15b mediates oxaliplatin‐induced chronic neuropathic pain through BACE1 down‐regulation - Ito, Naomi (Br J Pharmacol, 2017)
BACKGROUND AND PURPOSE: Although oxaliplatin is an effective anti‐cancer platinum compound, it can cause painful chronic neuropathy, and its molecular mechanisms are poorly understood. MicroRNAs (miRNAs) are small non‐coding RNAs that negatively regulate gene expression in a sequence‐specific manner. Although miRNAs have been increasingly recognized as important modulators in a variety of pain conditions, their involvement in chemotherapy‐induced neuropathic pain is unknown. EXPERIMENTAL APPROACH: Oxaliplatin‐induced chronic neuropathic pain was induced in rats by i.p. injections of oxaliplatin (2 mg·kg(−1)) for five consecutive days. The expression levels of miR‐15b and β‐site amyloid precursor protein‐cleaving enzyme 1 (BACE1 also known as β‐secretase 1) were examined in the dorsal root ganglion (DRG). To examine the function of miR‐15b, an adeno‐associated viral vector encoding miR‐15b was injected into the DRG in vivo. KEY RESULTS: Among the miRNAs examined in the DRG in the late phase of oxaliplatin‐induced neuropathic pain, miR‐15b was most robustly increased. Our in vitro assay results determined that BACE1 was a target of miR‐15b. BACE1 and miR‐15b were co‐expressed in putative myelinated and unmyelinated DRG neurons. Overexpression of miR‐15b in DRG neurons caused mechanical allodynia in association with reduced expression of BACE1. Consistent with these results, a BACE1 inhibitor dose‐dependently induced significant mechanical allodynia. CONCLUSIONS AND IMPLICATIONS: These findings suggest that miR‐15b contributes to oxaliplatin‐induced chronic neuropathic pain at least in part through the down‐regulation of BACE1.